Sustainability reporting standardization as a prerequisite for green post-war reconstruction of the agricultural sector; - Volodymyr Metelytsia (Sustainable Development of Economy, 2023)
The article is devoted to the study of standardization of sustainable development reporting in the context of granting Ukraine the status of a candidate for membership in the European Union and crisis phenomena related to Russian military aggression against Ukraine. It has been established that the implementation of Directives, Regulations, EU standards in the field of non-financial reporting determines the need for the formation of domestic legislation based on the principles of green transition and digital transformation. It was justified that the Report on Sustainable Development (Environmental, Social, Governance) and Investments (ESGI Report) should become one of the tools for attracting investments, loans, and insurance products in the post-war reconstruction of Ukraine's agricultural sector, taking into account global efforts aimed at preventing negative climate change and global warming. – – , , . , , ' , ' , . , , . , , ' . , , , ' , . , , . , , , . , (Report on sustainable development (Environmental, Social, Governance) and Investments, – ESGI Report) , , , . ESGI- , ; ' ' ; , , , , ' .
Keywords: 300; ESGI report; sustainability reporting platform; standardization; green investments; low-carbon technologies; social responsibility; GRI; TCFD; CDP initiatives; standards S1; S2; SASB; ESRS; Directive on corporate sustainability reporting (CSRD); ESGI-; GRI; TCFD; CDP; S1; S2; SASB; ESRS; CSRD